2021
DOI: 10.3390/su13126910
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding Variability in Droughts in Response to Extreme Climate Conditions over the Different Agro-Ecological Zones of Pakistan

Abstract: Here, we provided a comprehensive analysis of long-term drought and climate extreme patterns in the agro ecological zones (AEZs) of Pakistan during 1980–2019. Drought trends were investigated using the standardized precipitation evapotranspiration index (SPEI) at various timescales (SPEI-1, SPEI-3, SPEI-6, and SPEI-12). The results showed that droughts (seasonal and annual) were more persistent and severe in the southern, southwestern, southeastern, and central parts of the region. Drought exacerbated with slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…This phenomenon is frequently observed in modern cities worldwide, contributing to the broader issue of global urban heat islands (UHIs) (Sadik-Zada and Gatto, 2022). The meteorological characteristics of an area undergo degradation due to urbanization, resulting in increasing air temperatures, reducing rainfall, increasing relative humidity, and increasing energy consumption (Arshad et al, 2019;Dilawar et al, 2021a;Dilawar et al, 2021b;Ali et al, 2020;Ali et al 2021;Ali et al 2023;Dilawar et al, 2021c). Riaz et al (2014) revealed that Lahore's urban land area increased from 33.28% (58,977 ha) in 1972 to 55.97% (99,173 ha) in 2009, accompanied by a proportional decrease in green cover during the same timeframe (Riaz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is frequently observed in modern cities worldwide, contributing to the broader issue of global urban heat islands (UHIs) (Sadik-Zada and Gatto, 2022). The meteorological characteristics of an area undergo degradation due to urbanization, resulting in increasing air temperatures, reducing rainfall, increasing relative humidity, and increasing energy consumption (Arshad et al, 2019;Dilawar et al, 2021a;Dilawar et al, 2021b;Ali et al, 2020;Ali et al 2021;Ali et al 2023;Dilawar et al, 2021c). Riaz et al (2014) revealed that Lahore's urban land area increased from 33.28% (58,977 ha) in 1972 to 55.97% (99,173 ha) in 2009, accompanied by a proportional decrease in green cover during the same timeframe (Riaz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Such variability has profound implications for water resource management, agriculture, and overall ecosystem services. Studies have shown that while some regions are experiencing a decrease in precipitation, others may see an increase, further complicating the management strategies required to address these changes [43,44].…”
Section: Study Areamentioning
confidence: 99%
“…Aerosol optical depth retrievals from multiple satellite algorithms were calibrated based on Aerosol Robotic Network (AERONET) observations (https://sedac.ciesin.columbia.edu (10 September 2022)) [63,64]. Three meteorological parameters (temperature maximum, temperature minimum, and precipitation) were obtained from the Fifth generation (ERA5) (https://www.ecmwf.int/en, accessed on 28 September 2022) [82][83][84] as in the description written for Table 1. Ground measurements were used to compare the satellite-estimated and NASA SEDAC data at some pollution monitoring stations as different locations as indicated in Figure 1.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Meanwhile, the MK test assumes that time series have no sequential correlation and is based on the assumption that all data are significant [88]. These techniques are widely used to analyze climatic parameters in particular [82,89].…”
Section: Trend Analysismentioning
confidence: 99%